Identification of an active metabolite of PAR-1 antagonist RWJ-58259 and synthesis of analogues to enhance its metabolic stability. Issue 12 (1st March 2016) - Robinson, Eifion; Knight, Emily; Smoktunowicz, Natalia; Chambers, Rachel C.; Inglis, Graham G.; Chudasama, Vijay; Caddick, Stephen
Abstract : Understanding the pharmacokinetic behaviour of PAR-1 antagonist RWJ-58259 and the synthesis of analogues to enhance metabolic stability. Abstract : The discontinuation of PAR-1 antagonist RWJ-58259 beyond use as a biological probe is most likely due to it's short half-life in vivo . However, retention of significant in vivo activity beyond the point where most of the RWJ-58259 had been consumed implies the generation of an active metabolite. Herein we describe the biological activity of a predicted metabolite of RWJ-58259 and the synthesis of analogues designed to enhance the metabolic stability of RWJ-58259.